It's time
With two women's world cups and a world series on the horizon in Aotearoa, Sport NZ has launched "It`s Time" - a campaign aimed at promoting greater engagement in elite women`s sport. Research commissioned by Sport NZ shows awareness of female athletes is significantly lower than comparable male athletes, particularly in team sports. Key Research insights: Awareness of female athletes is significantly lower than comparable male athletes which impacts the marketability of women`s sport. In team sports in particular, awareness of female athletes is well below that of male athletes. Only 1 in 3 New Zealander`s watch women`s sport regularly. At a total population level, close to half haven`t changed their behaviours towards women`s sport in the last five years - i.e. attending live sport, watching live sport, following on media or social media or talking about it with family and friends. 53% of New Zealanders believe they won`t change their behaviour in regards to how they engage with women`s sport over the next 12 months. The biggest barrier to watching women`s sport is not knowing enough about events, teams or athletes. It's now time for researching the gender gap ant to give support to women`s sport.